Computational engineering of low bandgap copolymers - Wykes, Michael; Milián-Medina, Begoña; Gierschner, Johannes (Frontiers in Chemistry, 2013)
We present a conceptual approach to low bandgap copolymers, in which we clarify the physical parameters which control the optical bandgap, develop a fundamental understanding of bandgap tuning, unify the terminology, and outline the minimum requirements for accurate prediction of polymer bandgaps from those of finite length oligomers via extrapolation. We then test the predictive power of several popular hybrid and long-range corrected DFT functionals when applied to this task by careful comparison to experimental studies of homo- and co-oligomer series. These tests identify offset-corrected M06HF, with 100% HF exchange, as a useful alternative to the poor performance of tested hybrid and long-range corrected functionals with lower fractions of HF exchange (B3LYP, CAM-B3LYP, optimally-tuned LC-BLYP, BHLYP), which all significantly overestimate changes in bandgap as a function of system size.